Repair of airway epithelia requires metabolic rewiring towards fatty acid oxidation - Stefania Crotta; Matteo Villa; Jack Major; Katja Finsterbusch; Miriam Llorian; Peter Carmeliet; Joerg Buescher; Andreas Wack (Nature Communications, 2023)
Airway epithelial repair, a key process in the recovery from lung injury, requires a metabolic shift from glycolysis to fatty acid oxidation (FAO). Pharmacological FAO promotion enhances epithelial differentiation, suggesting new therapeutic options.